Anandamide and cyclooxygenase-2 regulate the interaction between endometrial fibroblast and endothelial cells. - Cañumil, Vanesa Alejandra (2022)
During pregnancy, an adequate uterine blood flow is required to ensure the formation of the placenta and the delivery of oxygen and nutrients to the developing embryo. This change in blood flow is the result of the process of angiogenesis and remodeling of the maternal vessels.